Exploring the relations between the physiological factors and the likelihood of accidents on construction sites. Issue 1 (9th March 2021) - Kazar, Gökhan; Comu, Semra
Abstract : Purpose: Construction work involves high-risk activities and requires intense focus and physical exertion. Accordingly, working conditions at construction sites contribute to physical fatigue and mental stress in workers, which is the primary cause of accidents. This study aims to examine the relation between construction accidents and physiological variables, indicative of physical fatigue and mental stress. Design/methodology/approach: Four different real-time physiological values of the construction workers were measured including blood sugar level (BSL), electrodermal activity (EDA), heart rate (HR) and skin temperature (ST). The data were collected from 21 different workers during the summer and winter seasons. Both seasonal and hourly correlation analyses were performed between the construction accidents and the four physiological variables gathered. Findings: The analysis results demonstrate that BSL values of the workers are correlated inversely with construction accidents taking place before lunch break. In addition, except BSL a significant seasonal association between the physiological variables and construction accidents was found. Originality/value: It is disclosed that variations in physiological risk factors at certain working periods pose a high risk for construction workers. Therefore, efficient work-cycle rests can be arranged to provide frequent but short breaks for workers to overcome such issues. Besides, an early warning system could be introduced to monitor the real-time physiological values of the workers.